Appropriateness of frequent use of emergency departments: A retrospective analysis in Rome, Italy - Furia, Giuseppe; Vinci, Antonio; Colamesta, Vittoria; Papini, Paolo; Grossi, Adriano; Cammalleri, Vittoria; Chierchini, Patrizia; Maurici, Massimo; Damiani, Gianfranco; De Vito, Corrado (Frontiers in Public Health, 2023)
BACKGROUND: Frequent users (FUs) are patients who repeatedly and inappropriately attend the Emergency Department (ED) with low-grade symptoms that could be treated outside the hospital setting. This study aims to investigate the phenomenon of the FU in Rome by profiling such users and analysing ED attendances by FUs. METHODS: The analysis was carried out for attendances in 2021 at 15 EDs in the Local Health Authority Roma 1 geographical area. A digital app collected data, including information on the following variables: number of attendances, demographic characteristics, emergency medical service (EMS) usage, triage code, and appropriateness of attendance. Covid-19 diagnosis was also studied to analyse any possible influence on ED attendance. Differences between FUs and non-FUs were investigated statistically by t-test and χ2-test. Univariate analysis and multivariable logistic regression were performed to analyse the associated factors. RESULTS: A total of 122,762 ED attendances and 89,036 users were registered. The FU category represented 2.9% of all users, comprising 11.9% of total ED attendances. There was a three-times higher frequency of non-urgent codes in attendances of FU patients (FU: 9.7%; non-FU: 3.2%). FUs were slightly more likely to have used the EMS (13.6% vs 11.4%) and had a lower frequency of appropriate ED attendance (23.8% vs 27.0%). Multivariate logistics analysis confirmed a significant effect of triage code, gender, age, EMS usage and Covid-19 diagnosis for the appropriateness of attendances. The results were statistically significant (p <0.001). CONCLUSION: The FU profile describes mostly non-urgent and inappropriate attendance at the ED, including during the Covid-19 pandemic. This study represents an important tool for strengthening preventive policies outside the hospital setting. The Italian National Recovery and Resilience Plan represents an excellent opportunity for the development of new strategies to mitigate the phenomenon of FUs.